Relationship among morphology, photoluminescence emission, and photocatalytic activity of Eu-doped ceria nanostructures: A surface-type effect - Ortega, P. P. [UNESP]; Amoresi, R. A.C. [UNESP]; Teodoro, M. D.; Longo, E.; Ponce, M. A.; Simões, A. Z. [UNESP] (Elsevier, 2023)
Herein, we discuss the synthesis of Eu-doped ceria nanostructures via the microwave-assisted hydrothermal method. The morphological analysis showed that Eu-doped ceria nanoparticles, nanorods, nanocubes, and nanopolyhedrons with different sets of exposed facets were obtained. The structural characterization revealed that the samples were crystalline and without secondary phases. The optical analysis showed a decrease in the bandgap energies of the Eu-doped nanostructures compared with pure ceria nanoparticles, and different photoluminescence emissions were found depending on the morphology. The photocatalytic activity of each nanostructure was evaluated, and Eu-doped nanopolyhedrons were the most promising photocatalyst, exhibiting a 60% and 80% increase in RhB discoloration compared to the Eu-doped and pure ceria nanoparticles, respectively. The better performance of the nanopolyhedrons is probably associated with the presence of different exposed facets, such as (111), (200), (220), and (311). The main species involved in the photocatalytic process were holes. The performances of each nanostructure were associated with their different exposed facets, the concentration of oxygen vacancies, and surface defects.
Keywords: Cerium dioxide; Morphology; Nanostructures; Photocatalysis; Rare-earth